Technological Approaches in Applied Social learning: (Formulate in lieu of industry 4.0) - Umachandran, Krishnan; P, Amuthalakshmi; T, Roosefert Mohan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
Industry 4.0 covers the readiness of achieving expertise that impacts the society, strategy, talent and technology. Individual, social and economic demands pose ever-changing challenges for education and training even in today’s world. In spite of the shrinking rapidity, which progressively affects the cognitive, biological, and information offerings into the new insights on people learning, for an effective reformation to an even more miniature of scientific and technological connect, ultimately on the knowledge content. Today’s students will compete in a technological, diverse, multi-cultural world and must be prepared to thrive in that futuristic environment; therefore, it is vital that today’s pedagogy produce lifelong learners, who can succeed in a global arena. To ensure our educational technology progresses at the rate demanded by today’s ubiquitous digital learners, we are reviewing emerging technologies and traditional teaching methods and propose desirable changes. Further enhancement in student learning and outcomes through technology enabled learning builds alliances among institutional units, employers, community partners and provides the effective delivery of learning services and opportunities to students. Technology depends on the cleverness and the innovative application of theoretical tools from control and estimation for scalability through hierarchy and multi-modality. Educational technology enhances the learning experience for students, faculty, the university and community at large. Hence, to develop a richer context for student learning, covering societal inadequacies, injustices in empowerment to learning access among students, cross-cultural involvements, and opportunity to learn, we deliberate on the latest trends in pedagogy - intelligent tutoring systems and ICT integration that can be modified during their implementation to suit future needs for industry 4.0 requirements.